Profil Pasien Eritroderma di Rumah Sakit Pertamina Bintang Amin Periode Januari 2016 – Desember 2019 - Arif Effendi; Eka Silvia; M. Syafei Hamzah; M. Ridho Noverliansyah (Puslitbang Sinergis Asa Professional, 2021)
Erythroderma is an inflammation of the skin that affects 90% or more of the skin surface area, and can be accompanied by squama. Several case reports found the incidence of erythroderma in men is greater than in women, with cases 2:1 to 4:1, and an average age of 41–61 years. Erythrodermic therapy must be adapted to the conditions of the disease. The mortality rate depends on the cause of erythroderma. Due to the lack of research data on erythroderma, researchers want to see more of the characteristics of the disease. Objectives To determine the profile of Erythroderma patients at Pertamina Bintang Amin Hospital in the period 2 January 2016 - 31 December 2019. Method This study used an observational descriptive method with a retrospective design, sampling with total sampling. Results This study showed that the highest incidence of erythroderma occurred in 2016 many as 11 people (50.0%). The majority of erythrodermic patients were male many as 13 people (59.1%). Erythrodermic patients >60 years of age occupy the highest position in the age distribution many as 14 people (63.6%). The highest cause of erythroderma was the expansion of the disease by 11 people (50.0%). Management mostly given to erythrodermic patients was oral corticosteroids + moisturizers + antihistamines as many as 12 people (54.5%).Conclusion: Highest incidence in 2016, Erythrodermic patients >60 years of age occupy the highest ,The majority of erythrodermic patients were male, cause of erythroderma was the expansion of the disease, Management mostly given to erythrodermic patients was oral corticosteroids + moisturizers + antihistamines.